Implementasi automasi perpustakaan: Studi kasus di Fakultas Adab dan Humaniora Universitas Islam Negeri Imam Bonjol - Sefri Doni (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
Adab Faculty Library and Humanities are the only of 6 faculties and postgraduate libraries in Imam Bonjol Padang UIN that succeed in developing library services based on information and communication technology. The results showed that this success was achieved thanks to the solid collaboration of various parties, including leaders, educators, students and librarians. In addition to solid cooperation the next thing that affects the success of the implementation of library automation in the faculty of adab and humanities is the spirit of learning and the power of a high librarian.